Early-type galaxy density profiles from IllustrisTNG – II. Evolutionary trend of the total density profile. Issue 4 (18th October 2019) - Wang, Yunchong; Vogelsberger, Mark; Xu, Dandan; Shen, Xuejian; Mao, Shude; Barnes, David; Li, Hui; Marinacci, Federico; Torrey, Paul; Springel, Volker; Hernquist, Lars
ABSTRACT: We study the evolutionary trend of the total density profile of early-type galaxies (ETGs) in IllustrisTNG. To this end, we trace ETGs from z = 0 to 4 and measure the power-law slope γ′ of the total density profile for their main progenitors. We find that their slopes γ′ steepen on average during z ∼ 4–2, then becoming shallower until z = 1, after which they remain almost constant, aside from a residual trend of becoming shallower towards z = 0. We also compare to a statistical sample of ETGs at different redshifts, selected based on their luminosity profiles and stellar masses. Due to different selection effects, the average slopes of the statistical samples follow a modified evolutionary trend. They monotonically decrease since z = 3, and after z ≈ 1, they remain nearly invariant with a mild increase towards z = 0. These evolutionary trends are mass dependent for both samples, with low-mass galaxies having in general steeper slopes than their more massive counterparts. Galaxies that transitioned to ETGs more recently have steeper mean slopes as they tend to be smaller and more compact at any given redshift. By analysing the impact of mergers and AGN feedback on the progenitors' evolution, we conjecture a multiphase path leading to isothermality in ETGs: dissipation associated with rapid wet mergers tends to steepen γ′ from z = 4 to 2, whereas subsequent AGN feedback (especially in the kinetic mode) makes γ′ shallower again from z = 2 to 1. Afterwards, passive evolution from z = 1 to 0, mainly through gas-poor mergers, mildly decreases γ′ and maintains the overall mass distribution close to isothermal.